Fixed Capital Adjustment : Is Latin America Different? Evidence from the Colombian and Mexican Manufacturing Sectors - Gelos, R.; Isgut, Alberto (Washington, D.C. : International Monetary Fund, 1999)
This paper examines capital adjustment patterns using two large and largely novel data sets from the manufacturing sectors of Colombia and Mexico. The findings show that investment patterns in these countries resemble those reported for the United States to a surprising extent. Capital adjustments beyond maintenance investment occur only rarely, but large spikes account for a significant fraction of total investment. Although duration models do not provide strong evidence for the presence of substantial fixed costs, nonparametric adjustment function estimates reveal the presence of irreversibilities in investment. These irreversibilities are important for understanding aggregate investment behavior.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet